COMMUNITY EMPOWERMENT IN UTILIZING YARD LAND TO SUPPORT VILLAGE FOOD SECURITY IN THE COVID-19 ERA - Kaiwai, Orgenes; Tuhuteru, Sumiyati; Wilil, Frengki; Douw, Lince; Wandikbo, Oni; Kogoya, Itamius; Agapa, Rut; Walela, Fia; Matuan, Erius; Tabuni, Ilince; Karoba, Yopi; Karoba, Diton; Mabel, Rosalina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Increasing national food security needs to be built from food security at the household scale. Household-scale food security means that each family can meet their food needs independently. The yard of the house is the closest area that can be used by households for cultivating food crops, such as vegetables and fruits. The purpose of this work program is to stimulate productive community activities in the era of the COVID-19 pandemic, increase public awareness to take advantage of unused yards, increase independent food security, especially among families, and increase the entrepreneurial spirit of the community by utilizing local food that is around and increase the value of the community. plus. This service activity was carried out in Kama Village, Wesaput District, Jayawijaya Regency, Papua Province which lasted for ± 1 month at the same time as the STIPER Petra Baliem Wamena Real Work Lecture Program Batch XIII 2021/2022. The results of the activity show that the application of the use of yard land can be applied in the community of Kama Village so that the community can be self-sufficient in food and able to utilize materials that are easily found as planting containers, the basic ingredients of vegetable pesticides and cattle waste fertilizers that are commonly encountered and are able to improve aesthetics in the house environment.